Ethno-Political Dynamism and Its Role in the Development of Indonesian Islamic Banking Law - Dahlan, Ahmad; Voak, Adam; Chin, James; Mariyani-Squire, Edward; Aprianto, Naerul Edwin Kiky (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
Studies on Indonesia's political conditions during the New Order until the 1990s reveal a significant shift in political dynamics, transitioning from a stance largely closed to Islamic interests to one that increasingly accommodated Islam through specific policies. This article aims to determine the influence of the ethnopolitical dynamics of Islam formed by the New Order on the development of Islamic banking law and its impact on the financial sector in Indonesia. Through a historical and contextual literature review, supplemented by interviews, it was observed that ethnopolitical dynamics significantly influenced the evolution of Indonesian banking law during and after that period. The influence of Islamic ethnopolitics, particularly in academic circles, has increasingly emerged as a dynamic force in facilitating the development of Islamic banking in Indonesia, underscoring the numerous challenges encountered in achieving market acceptance. Although its growth has not met market expectations, ethnopolitically, Islam continues to lobby for Islamic banking regulations. Furthermore, since 2019, the role of ethnopolitics has continued to realize policy and regulatory responses aimed at encouraging the growth of Islamic finance in Indonesia.